Analysis of Student Manners Towards Teachers from the Perspective of Surah Al-Hujurat Verses 1-5 and Its Implementation at the Miftahul Huda Al-Burhani Plered Purwakarta Islamic Boarding School - Husny Fauzy; Debibik Nabilatul Faujizah; Neng Ulya (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study examines students' adab towards teachers at Miftahul Huda Al-Burhani Islamic Boarding School, focusing on verses 1-5 of Al-Hujurat Surah. Through the examples given by its teachers, Miftahul Huda Al-Burhani Islamic Boarding School encourages the growth of adab or morals. This study shows that students have good morals, are polite, and are sensitive to teachers. This subject is closely related to the contemporary educational and social situation in Indonesia. The values of the Qur'an must be practiced in learning to help shape students' moral character and improve the learning environment. This study supports the role of teachers as moral and ethical leaders. In addition, this study examines how Islam teaches respect for teachers and its findings can be used to improve educational practices and social norms. As a result, this study directly contributes to initiatives aimed at improving educational standards and shaping the mindset of Indonesian youth. The method used by the researcher is a qualitative approach with a library research type and is strengthened by data collection techniques through observation, interviews and documentation. The interpretation of the Qur'an and Hadith is the primary source of research data. The researcher uses several scientific literature and studies related to the manners of students towards teachers as secondary sources. Among them are: books, scientific works, journals and several books written by previous scholars. As for the data analysis technique, the researcher uses data reduction, data presentation, and conclusions. In this study, the results obtained regarding the manners of students towards teachers in the perspective of the letter Al-Hujurat verses 1-5 from several interpretations taken, namely the interpretation of Al-Qurthubi, Al-Azhar, and Al-Misbah. From the analysis of student manners towards teachers from the perspective of Surah Al-Hujurat verses 1-5, there are 5 points including: asking for opinions from teachers, not raising their voices when talking to teachers and not calling teachers like friends, lowering their voices to teachers, asking permission from teachers, and being patient with teachers. From the implementation of student manners towards teachers at the Miftahul Huda Al-Burhani Plered Purwakarta Islamic Boarding School, researchers can explain that students here always ask for opinions from teachers, obey the rules in the Islamic Boarding School, do not raise their voices when talking to teachers, do not call teachers like friends, ask permission from teachers, and be patient with teachers. One of the main values taught at the Miftahul Huda Al-Burhani Islamic Boarding School is not only forming a good relationship between students and teachers, but also plays an important role in the success of education and the formation of student character. At the Islamic Boarding School, this manner is seen as the key to gaining useful and blessed knowledge in life.